Lipophosphonoxins II: Design, Synthesis, and Properties of Novel Broad Spectrum Antibacterial Agents - Seydlová, Gabriela; Pohl, Radek; Zborníková, Eva; Ehn, Marcel; Šimák, Ondřej; Panova, Natalya; Kolář, Milan; Bogdanová, Kateřina; Večeřová, Renata; Fišer, Radovan; Šanderová, Hana; Vítovská, Dragana; et al. (Journal of medicinal chemistry, 2017)
The increase in the number of bacterial strains resistant to known antibiotics is alarming. In this study we report the synthesis of novel compounds termed Lipophosphonoxins II (LPPO II). We show that LPPO II display excellent activities against Gram-positive and -negative bacteria, including pathogens and multiresistant strains. We describe their mechanism of action-plasmatic membrane pore-forming activity selective for bacteria. Importantly, LPPO II neither damage nor cross the eukaryotic plasmatic membrane at their bactericidal concentrations. Further, we demonstrate LPPO II have low propensity for resistance development, likely due to their rapid membrane-targeting mode of action. Finally, we reveal that LPPO II are not toxic to either eukaryotic cells or model animals when administered orally or topically. Collectively, these results suggest that LPPO II are highly promising compounds for development into pharmaceuticals.
Keywords: Cell Survival; buněčná membrána; pyrazoly; Microbial Sensitivity Tests; Lipid Bilayers; stereoizomerie; Apoptosis; Humans; mnohočetná bakteriální léková rezistence; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; mikrobiální testy citlivosti; testy kožní dráždivosti; lidé; antibakteriální látky; zvířata; Stereoisomerism; Drug Resistance, Multiple, Bacterial; apoptóza; Drug Design; buněčné linie; Mice, Inbred ICR; lipidové dvojvrstvy; uridinmonofosfát; Cell Line; Anti-Bacterial Agents; Male; Phospholipids; racionální návrh léčiv; Gram-Negative Bacteria; nádorové buněčné linie; králíci; Uridine Monophosphate; grampozitivní bakterie; fosfolipidy; Animals; Cell Line, Tumor; Cell Membrane; myši inbrední ICR; Gram-Positive Bacteria; mužské pohlaví; Pyrazoles; Rabbits; Skin Irritancy Tests; viabilita buněk; gramnegativní bakterie